Its a question of chaining/glueing the axioms between them.
Let's start from the end:
$$\mathbf{\{s == p * (p + 1) / 2\}}$$
Use the strengthening rule to change the postcondition to
$$\mathbf{\{s == p * (p + 1) / 2 \wedge p == n \wedge p >= 0\}} $$
which is equivalent to
$$\mathbf{\{s == n * (n + 1) / 2 \wedge p == n \wedge p >= 0\}}$$
By the Loop rule in order for the triple:
$$ \mathbf{\{s == n * (n + 1) / 2 \}} \mathtt{while}\ (n <= p)\ \{s = s + n ;
n = n + 1\} \mathbf{\{s == n * (n + 1) / 2 \wedge p == n \}}
$$
we need to prove that the triple
$$\mathbf{\{s == n * (n + 1) / 2 \}} \{s = s + n ;
n = n + 1\} \mathbf{\{s == n * (n + 1) / 2\}}$$
is valid.
Let then use the composition to reduce this to proving that the two following triples are valid:
$$\mathbf{\{s == n * (n + 1) / 2 \}}
\{s = s + n\}
\mathbf{\{s == (n+1) * (n + 2) / 2\}}$$
and
$$\mathbf{\{s == (n+1) * (n + 2) / 2 \}}
\{ n = n + 1\}
\mathbf{\{s == n * (n + 1) / 2\}}$$
The latter one is just an application of the Assignment rule (just replace the occurrences of $n$ by $n+1$ in the postcond to get the precondition).
To prove the first one, we need to apply Strengthening to reduce it to the triple
$$\mathbf{\{s == n * (n + 1) / 2 \}}
\{s = s + n\}
\mathbf{\{s == (n) * (n +1) / 2 + n\}}$$
and then use the Assignment rule trivially.
Okay so now we only need (by Sequence rule) to prove that the triple
$$\mathbf{\{p>=0 \}} s:=0; n:= 1 \mathbf{\{s == n * (n + 1) / 2 \wedge p >= 0\}}$$
which can be done in the same way by splitting with sequence.